UNA UNIVERSIDAD AL SERVICIO DE LA INVESTIGACIÓN MULTIDISCIPLINARIA - Arrarte Mera, Raúl Alberto (2014)
This work is a proposal for settlement in the new con-text of the University Act No. 30220, published on July 9, 2014 for future members of the Statutory Assembly of the National University of San Marcos, who shall be elected for the first time in the story of university life by direct, secret and universal vote by all undergraduate and graduate students as well as teachers and have the delicate responsibility of drafting and approving its Statute. The method used has been updating a doc-toral thesis subscribed approved 2005 entitled: “The University-Industry Cooperation-State in Peru (Case San Marcos 1997-2002)”, adapted to the requirements of the new law which established 16 chapters three additional transitional provisions, amendments and final. The objectives are: To promote multidisciplinary research, transparency and administrative simplifica-tion. Through its 11 structural organization charts, administrative proposes an institutional reengineering, now consists of 20 faculties, comprising only five (5) areas of expertise: Basic Sciences; Health Sciences; en-gineering; Economic Business and Humanities. A new simplified structure that will facilitate the effectiveness, efficiency and effectiveness in making economic and administrative decisions.